Association between vitamin K intake and depressive symptoms in US adults: Data from the National Health and Nutrition Examination Survey (NHANES) 2013–2018 - Zhang, Yuyi; Tan, Weiliang; Xi, Xiaolan; Yang, Hui; Zhang, Ke; Li, Shengnan; Chen, Xuefen; Zuo, Hui (Frontiers in Nutrition, 2023)
Background: The relationship between vitamin intake and depression has attracted increasing attention. However, only a few studies have focused on the relationship between vitamin K intake and depression at present. This study was aimed to investigate the cross-sectional association between vitamin K intake and depression in US adults. Methods: We used the data from a nationally representative sample of 11687 adults from the 2013-2018 National Health and Nutrition Examination Survey (NHANES). Vitamin K intake was assessed by 24-hour dietary recall. Depression status was assessed using the 9-item Patient Health Questionnaire (PHQ-9). Logistic regression and generalized additive model were used to examine the association between vitamin K intake and depression. Results: The overall prevalence of depression was 11.1% (8.9% in men and 13.1% in women). We observed a significant inverse linear relationship between vitamin K intake and depression in models adjusted for age, sex, race/ethnicity, marital status, educational status, family poverty income ratio (PIR), home status, body mass index (BMI), smoking status, sleep disorders, hypertension, hyperlipidemia, and diabetes. The OR (95% CI) for the highest compared with the lowest quartile of vitamin K intake was 0.64 (95% CI: 0.52, 0.80, P-trend <0.001). The association was similar in subgroups stratified by age, sex, race/ethnicity, marital status, educational status, PIR, home status, BMI, smoking status, sleep disorders, hypertension, hyperlipidemia, and diabetes. Conclusion: Vitamin K intake was inversely and independently associated with the odds of depression in the US adults. Prospective studies are warranted to confirm our findings.